2007
DOI: 10.1200/jco.2006.07.0805
|View full text |Cite|
|
Sign up to set email alerts
|

Screening for Coronary Artery Disease After Mediastinal Irradiation for Hodgkin's Disease

Abstract: Stress-induced signs of ischemia and significant coronary artery disease are highly prevalent after mediastinal irradiation in young patients. Stress testing identifies asymptomatic individuals at high risk for acute myocardial infarction or sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
132
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(144 citation statements)
references
References 40 publications
5
132
2
5
Order By: Relevance
“…Most of the patients with cardiac ischemia did not have anginal complaints. These findings are in agreement with the study of Marks et al [9], Heidenreich et al [13,14] and the Dutch Late Effects Breast Cancer Cohort, which studied the effects of cardiovascular toxicity of radiation therapy in women with breast cancer during a period of 10 years [15,16] and the SEER database [17]. The latter was a large study of women, who survived breast cancer treated with radiation therapy.…”
supporting
confidence: 89%
“…Most of the patients with cardiac ischemia did not have anginal complaints. These findings are in agreement with the study of Marks et al [9], Heidenreich et al [13,14] and the Dutch Late Effects Breast Cancer Cohort, which studied the effects of cardiovascular toxicity of radiation therapy in women with breast cancer during a period of 10 years [15,16] and the SEER database [17]. The latter was a large study of women, who survived breast cancer treated with radiation therapy.…”
supporting
confidence: 89%
“…Studies of cardiovascular function in symptomatic and asymptomatic HL survivors have shown increased frequency of valvular sclerosis and other aberrant findings. 6,[11][12][13][14][15] This is higher than reported in the general population. 16,17 It has been difficult to disentangle if these changes are clinically relevant and what investigations could be suitable for screening.…”
contrasting
confidence: 50%
“…The risk of radiation-induced secondary cancer in children with cholangiocarcinoma treated with RT was also found to be the highest after X-ray therapy, and the lowest after intensive proton therapy (69). The increased risk of coronary artery disease and valvular dysfunction was found to be associated with cardiac irradiation during X-ray treatment of Hodgkin's lymphoma (70,71). Therefore, in order to reduce the morbidity, mortality, pain and health care costs of Hodgkin's lymphoma survivors, PBT may be a feasible option.…”
Section: Pbt For Different Cancersmentioning
confidence: 85%